CREATION OF INFORMATION RESOURCES OF ENGINEERING PEDAGOGICAL REQUESTS FOR USERS: THE EXPERIENCE OF THE SCIENTIFIC LIBRARY OF THE UKRAINIAN ENGINEERING PEDAGOGICS ACADEMY - Nikolayenko, Natalia (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This paper presents the experience of the scientific Library of UIPA on questions related to the topics of scientific research in the state budget theme "System organization of information and bibliographic software development of engineering and teacher education." It provides information about its own sector-specific information resource with a single point of access.